Stakeholder management: How similar are the concepts of Business Diplomacy and Public Relations? - Falcão, P. F.; Ramalho, N. (29th EBES Conference - Lisbon, 2019)
Objectives: Stakeholder relations evolved from a traditional one-way information distribution Public Relations (PR) model to a two-way model (Mogensen, 2017). Alongside with this change the construct of Business Diplomacy (BD) emerged (Yiu & Saner, 2017) which seems to address this two-way information distribution model. However, the conceptual boundaries between PR and BD are yet unclear. To clarify the semantic boundaries, this study is set to empirically test the extent of conceptual overlap as well as the need for the emerging concept of BD into stakeholder management. Data & Method: Corporate representatives in charge of stakeholder management were invited to participate in an online survey measuring both PR and BD activities. With a sample of 104 companies we tested for construct validity via factorial analysis as well as convergent validity and divergent validity. We additionally tested for reliability of each factor. Results: The analyses showed a three-factor structure that mixed PR and BD activities into three functions: Communication, Influence, and Intelligence. The solution has acceptable AVEs for all factors as well as divergent validity (Fornell & Larcker, 1981). All scales showed good composite reliability values. These factors are differently associated with the importance given to stakeholders as shown by regression analyses where intelligence (Beta=.379, p<.01) and influence (Beta=.319, p<.01) are positively associated but communication is not. Conclusion: Findings suggest both concepts overlap but not to the point of indicating conceptual identity. BD emphasizes influence as a key function adding to intelligence and communication. At the light of theory, we interpret the inexisting association between communication and importance given to stakeholders as indicative of its fundamental role, a common denominator to all stakeholder management, while intelligence and influence operate as strategic differentiators. We conclude that BD adds to PR concept in managing stakeholders.